Effects of retention period on field emergence, seed vigour and genetic purity of soybeans (glycine max. l). - Mazviro, Crynos (Midlands State University, 2017)
Access to high quality certified soybeans seeds by most small scale commercial farmers is a major constraint and this result in most farmers to retain their seed obtained from the previous harvests. The aim of this study was to assess the effects of retention period on field emergence, vigor and genetic purity of soybean seeds under the smallholder farmers in semi arid regions of Zimbabwe. A survey was first conducted to assess the agronomic and storage practices done by smallholder farmers on soybeans. Questionnaires were used to gather data and it was during this time when seeds were collected from farmers for field experimentation. The experimental treatments were as follows: certified soybean seeds, retained seeds with one year, retained soybeans seeds with two years and retained soybean seeds with three or more years. The experiment was laid in a Randomised Complete Block Design with four treatments replicated three times. The blocking factor was slope. Laboratory test were then conducted to determine seed vigor and genetic purity. Accelerated Aging Test was used to determine seed vigor. The number of seedling emerged under vigor test were counted and then classified into strong, weak and abnormal seedlings. Genetic purity was determined by looking on the physical components of the sample. From the results gathered from a survey it was seen that most famers retain seeds obtained from their previous harvest and most of them produced an average yield of 0.6 tonnes per hectare. From the results obtained it was seen that retention period of soybeans significantly (p<0.001) affect seed emergence, vigor and genetic purity. It was also observed that germination percentage, germination uniformity, seed vigor and genetic purity decreases as retention period increases while mean germination time and days to 50 % emergence increases as retention period increases. A positive relationship was observed between seed viability and seed vigor on correlation analysis done. Farmers should not retain seeds stored for more than one year and also where retained seeds are used, higher seed rates should be used to compensate the low viability of retained seeds